A Comparison of Revision Rates and Patient-Reported Outcomes for a 2-Level Posterolateral Fusion Augmented With Single Versus 2-Level Transforaminal Lumbar Interbody Fusion. Issue 8 (December 2020) - Kaye, I. David; Fang, Terry; Wagner, Scott C.; Butler, Joseph S.; Sebastian, Arjun; Morrissey, Patrick B.; Levine, Marc J.; Vaccaro, Alex R.; Hilibrand, Alan S.
Study Design: Retrospective, single institution, multisurgeon case control series. Objective: To determine whether there are differences in reoperation rates or outcomes for patients undergoing 2-level posterolateral fusion (PLF) augmented by a transforaminal lumbar interbody fusion (TLIF) at only one of the levels or at both. Methods: A total of 416 patients were identified who underwent 2-level PLF with a TLIF at either one of those levels (n = 183) or at both (n = 233) with greater than 1-year follow-up. Demographic, surgical, radiographic, and clinical data was reviewed for each patient. These included age, sex, race, body mass index, smoking status, Charleston Comorbidity Index, operative time, estimated blood loss, length of stay, and patient-reported outcome measures. Results: Each cohort underwent 24 reoperations. Although the number of overall reoperations was not significantly different ( P > .05), among the reoperation types, there were significantly more reoperations for adjacent segment disease in the 2-level group compared to the 1-level group (19 vs 12, P = .04). There was no difference in reoperation for pseudarthrosis between the groups ( P > .05). Although both groups experienced significant improvements in Oswestry Disability Index ( P < .001) and Short Form–12 health questionnaire ( P < .001), there were no differences between improvements for 1- versus 2-level cohorts. Conclusions: For patients undergoing 2-level PLF in the setting of a TLIF, using a TLIF at one versus both levels does not seem to influence reoperation rates or outcomes. However, reoperation rates for adjacent segment disease are increased in the setting of a 2-level PLF augmented by a 2-level TLIF.